Trajectories of COVID-19 pandemic-related depressive symptoms and potential predictors: the FinnBrain Birth Cohort Study - Li, Ru (SPRINGER HEIDELBERG, 2025)
Purpose: In the context of the COVID-19 pandemic, mental health problems have been reported, and parents of young children may be more vulnerable to psychological distress due to increased caregiving responsibilities. However, research on the heterogeneity of the longitudinal course of psychological symptoms during the pandemic and the predispositions linked with these courses is still scarce. This study aimed to identify differential trajectories of depressive symptoms among the parents of young children and investigate the role of temperament traits, alexithymia, and coping styles in the heterogeneity of the symptom trajectories.
Methods: The sample consists of 844 parents from the FinnBrain Birth Cohort Study. Latent growth mixture modeling was utilized to identify trajectories of depressive symptoms from pre-pandemic between 2014 and 2019 (T0, the closest available measurement was used) to May/June 2020 (T1) and December 2020 (T2) during the pandemic. Multinomial logistic regression was used to examine temperament, alexithymia, and coping as predictors of symptom trajectories, controlling for various background factors.
Results: Four trajectories of depressive symptoms were identified. Most parents experienced low and stable depressive symptoms. Negative affect, effortful control, alexithymia, emotion-diverting coping (self-distraction and venting), and avoidant coping (denial and behavioral disengagement) were predictors for subclinical stable depressive symptoms. Constructive coping (positive reframing, acceptance, and humor) protected the cohort parents from increasing or moderately high depressive symptoms.
Conclusions: The findings have implications for identifying vulnerable individuals with specific traits and strengthening of constructive coping strategies as possible foci in interventions for depression during global crises.